Qualidade das águas superficiais de reservatórios e principais tributários : estudo de caso do Reservatório da Usina Hidrelétrica de Irapé - MG - Karla Lorrane de Oliveira (2020)
This research used nonparametric and multivariate statistical techniques, calculation of the CCME water quality index (CCMEWQI) and analysis of violations of legislation and trends in data from water quality monitoring, in order to evaluate water quality of the Irapé UHE reservoir and its tributaries, from a spacetime perspective, relating the variations observed with the types of environments (lentic and lotic) and the use of the basin's soil. Cluster multivariate analysis separated the stations into two groups, according to their location and the type of the environment in which they are located. The results of the Kruskal Wallis nonparametric test, followed by the multiple comparison test, together with the boxplot graphs, suggested better water quality in the group formed by stations located in the reservoir and nearby. Related to the violation, the parameters of dissolved iron, BOD, PT and pH showed nonconformities at least once in all seasons and in every year of the historical series, specially the dissolved iron , for presenting an increasing trend of 64,3% in the monitoring stations. Despite the observed nonconformities, 61,3% of the 88 calculated CCMEWQI were classified as “good” and 29,5% as “acceptable”, indicating in general that the quality of the water analyzed is adequate for the proposed uses for Class 2 in Brazil, which are waters that can be consumed after simplified treatment. Furthermore, the seasonality influence analysis showed that the CCMEWQI for the rainy season remained in the same range in 43% of the monitoring stations and decreased in 57% of them, when compared to the dry season, which may be due to the propensity greater supply of nutrients as a result of the greater transport of allochthonous material to the water bodies. The soil use follows the pattern for the areas of influence of the monitoring stations studied, with emphasis on the uses of “natural forest”, which can be associated with the good index results obtained, “agriculture and livestock” and “reforestation”, which can be related to the high values of percentage of violation obtained for PT.